ASSOCIATION OF HIF1A rs142179458 WITH BODY ADIPOSITY IN MULTI-ETHNIC ASIANS WITH TYPE 2 DIABETES - Pandian, Bhuvaneswari; Moh, Angela; Ang, Keven; Subramaniam, Tavintharan; Sum, Chee Fang; Lim , Su Chi (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVES Hypoxia is known to contribute to obesity and its related metabolic disorders. Our preliminary data derived from whole-exome sequencing suggested an association of the hypoxia-inducible factor 1 a (HIF1a) rs142179458 variant with type 2 diabetes (T2D). However, the impact of this HIF1a variant on adiposity remains unclear. The study sought to identify the relationship between the HIF1a rs142179458 and the obesity phenotype. METHODOLOGY The study involved participants from the Singapore study of macro-angiopathy and microvascular reactivity in type 2 diabetes (SMART2D) study ( (n=2010; age =57±11; 51.3% males). The subjects were screened for the possibly damaging HIF1a rs142179458 (c.1045g>a [p. asp349asn]) variant [minor allele frequency: 0.00459 (all), 0.02719 (East Asians)] in genome-wide genotyping. The association of the HIF1a genotype with anthropometric variables was assessed using Chi-square test, Pearson’s correlation, and regression analyses. RESULTS Among the subjects, 2.5% ( (n=50) carried the HIF1a variant (ag/aa) and displayed higher body mass index (BMI) than the wildtype genotype (29.8±6.9 versus 27.6±5.2 kg/m p=0.004). Hip circumference and percentage body fat were also markedly higher in the former group. A positive correlation was observed between the HIF1a variant and the anthropometric parameters analyzed (all p<0.05). HIF1a variant was associated with BMI using the Asian BMI cut-off of 23.5 kg/m² even after adjusting for age, gender, and ethnicity (odds ratio:1.21, 95% CI:0.99-1.47, P=0.020). CONCLUSION HIF1a rs142179458 variant is associated with increased adiposity in adults with T2DM. We postulate that alteration in HIF1a gene may cause dysregulation of the adaptive response to hypoxia, resulting in body mass index gain and potentially aggravating diabetes.